Leadership Quality in Improving Graduate Quality at Madrasah Aliyah Hidayatul Insan Palangka Raya - Usup Kurniawan; Siminto; Zaitun Qamariah (English Education Journal, 2024)
Effective leadership is a crucial factor in the success of educational institutions, especially in improving the quality of student graduates. This study aims to explore the processes of planning, implementation, evaluation, and follow-up of leadership at Madrasah Aliyah Hidayatul Insan Palangka Raya in improving the quality of graduates. Using a descriptive qualitative research design, this study involved interviews, documentation, and observations during class meetings for data collection, focusing on the head of the Madrasah and two English teachers as subjects, as well as involving students' parents and alumni. The research findings reveal various strategies implemented by the head of the Madrasah and English teachers to improve the quality of graduates, covering all stages of leadership: planning, implementation, evaluation, and follow-up. Specifically, the leadership strategies include setting graduation standards that require students to meet certain criteria, such as passing Madrasah and Pondok exams, producing scientific papers, completing practical worship exams, and demonstrating proficiency in Arabic and English. The head of the Madrasah and English teachers actively guide students through these requirements, ensuring that they are prepared for their future educational endeavors. This research emphasizes the importance of collaborative leadership in creating an environment that supports academic success and continuous improvement in the quality of education.